Early neurological deterioration during the acute phase as a predictor of long-term outcome after first-ever ischemic stroke. Issue 51 (December 2017) - Geng, He-Hong; Wang, Qiang; Li, Bo; Cui, Bin-Bin; Jin, Yong-Ping; Fu, Rong-Li; Zhang, Qing; Wang, Jing-Jie; Wang, Pei-Xi
Abstract : Abstract: Early neurological deterioration (END) is associated with increased risk of functional disability and mortality. However, data are limited regarding the long-term risk of poor functional outcomes. Thus we explored the association between END and long-term outcomes in patients with acute ischemic stroke. A total of 1064 patients were enrolled with acute ischemic stroke who were consecutively admitted to the 3 stroke units of Huai-He Hospital, Kaifeng, China. END was defined as an increment change of at least one point in motor power or total National Institute of Health Stroke Scale (NIHSS) score deterioration ≥2 points within the first week after admission. We retrospectively assessed the risk factors of END and prospectively explored the relationship between END and the long-term outcomes by multivariable regression models after adjusting the potential confounding factors. Outcomes were evaluated at 18 months based on modified Rankin scale (MRS) scores. Approximately 32% of first-ever ischemic stroke patients experienced END during the acute phase. END was associated with diabetes (odds ratio [OR], 2.218; 95% confidence interval [CI] 1.619–3.037), NIHSS score at admission (OR, 1.052; 95% CI 1.023–1.082), C-reactive protein (CRP) levels (OR, 1.224; 95% CI 1.066–1.406]), and homocysteine (HCY) levels (OR, 1.203; 95% CI 1.061–1.365) after adjusting related factors, such as hypertension, diabetes, NIHSS at admission, and some blood laboratory values, including direct bilirubin, total cholesterol, low-density lipoprotein, glucose, CRP, HCY, and D-dimer levels. During the follow-up period, 52 (4.9%) patients died, 160 (15.0%) recrudesced, and 317 (29.8%) suffered poor outcomes. Multivariate logistic regression analyses revealed that poor outcome was associated with END (OR, 3.366; 95% CI 2.495–4.542), age (OR, 1.028; 95% CI 1.015–1.041), body mass index (OR, 1.096; 95% CI 1.051–1.144), coronary heart disease (OR, 1.637; 95% CI 1.108–2.416), and CRP (OR, 2.474; 95% CI 1.840–3.326). The risk factors of END are multifaceted. Diabetes, NIHSS score at admission, CRP, and HCY are independent predictors of END. In addition, the results of this study indicate that END is an important predictor of poor functional outcome.